Iridoid Glycosides from Citharexylum quadrangular - I. Khalifa, Taha; D. El-Gindi, Omayma; A. Ammar, Hassan; M. El-Naggar, Dina (Asian Journal of Chemistry, 2010)
The first isolation of biologically active iridoid glycoside phlomiol, 5-deoxy pulchelloside, lamiide, durantoside I and lamidoside from Citharexylum quadrangular has been done. A revision in some of the NMR spectral assignments has also been made to confirm the structure of these compounds. The biological screening of the 70% aqueous ethanolic extract revealed a significant antiulcer, antihypertensive and hepatoprotective effect of these plants.